Simvastatin improves the healing of infected skin wounds of rats - Rego,Amália Cínthia Meneses do (2007)
PURPOSE: This study explores the potential of the simvastatin to ameliorate inflammation and infection in open infected skin wounds of rats. METHODS: Fourteen Wistar rats weighing 285±12g were used. The study was done in a group whose open infected skin wounds were treated with topical application of sinvastatina microemulsion (SIM, n=7) and a second group with wounds treated with saline 0.9 % (SAL, n=7). A bacteriological exam of the wounds fluid for gram positive and gram negative bacteria, the tecidual expression of TNFá and IL-1â by imunohistochemical technique, and histological analysis by HE stain were performed. RESULTS: The expression of TNFa could be clearly demonstrated in lower degree in skin wounds treated with simvastatin (668.6 ± 74.7 ìm²) than in saline (2120.0 ± 327.1 ìm²). In comparison, wound tissue from SIM group displayed leukocyte infiltration significantly lower than that observed in SAL group (p<0.05). Culture results of the samples taken from wound fluid on fourth post treatment day revealed wound infection in only one rat of group simvastatin (SIM), where Proteus mirabilis, Escherchia coli and Enterobacter sp were isolated. In the rats whose wounds were treated with saline (SAL), polymicrobial infection with more than 100,000 CFU/g was detected in all the wounds. CONCLUSION: In addition to its antiinflammatory properties, the protective effects of simvastatin in infected open skin wounds is able to reduce infection and probably has antibacterial action. The potential to treat these wounds with statins to ameliorate inflammation and infection is promising.